RASIO KEUANGAN DAN PENGARUHNYA TERHADAP HARGA SAHAM PERUSAHAAN YANG TERDAFTAR DI JAKARTA ISLAMIC INDEX - Hamidah Hendrarini (STIE Perbanas Surabaya, 2011)
The stock market can enhance the economic condition of a country. Therefore, the more developed and developing capital markets of a country, the more developed and developing country economy as well, or vice versa. In addition, fluctuations in stock prices that occurred in the capital market can provide the clues of the fervour or sluggishness in capital markets activities and the investor in buying or selling shares. In 2005 until 2008, the company's stock price fluctuations are listed at the Jakarta Islamic Index. This study aims to determine the influence of the Net Profit Margin (NPM), Quick Ratio (QR), Return on Equity (ROE), Earning Per Share (EPS) and the Department to Equity Ratio (DER) to share price on the company listed on the Jakarta Islamic Index (JII). The techniques used to determine the sample was purposive sampling because the researcher has the purpose or target to select a sample based on the considerations and on certain criteria. Based on these criteria, then there are 15 companies that can serve as the research. It uses multiple regression analysis. The results of analysis show that the variable Net Profit Margin, Return On Equity, Earning Per Share and Dept. to Equity Ratio partially have no significant effect on stock price, while the Quick Ratio variables have positive and significant impact on stock price.